Formation Mechanism of Strip Defects in Anodizing AA5252 Aluminium Alloy Sheets - Gao, Chong; Jiang, Zhongyu; Liu, Zhenshan; Zhao, Pizhi; Huang, Ruiyin; Wu, Yongfu; Yu, Kangcai (MATEC web of conferences, 2020)
Processed by sulfuric acid anodizing, several unexpected strip defects exhibited on the anodizing film of AA5252 aluminium alloy sheets. Their formation mechanism was studied in detail. The normal zone and strip zone were compared, with respect to surface brightness, porosity of anodizing film, and microstructures of the corresponding aluminium substrate tested by spectroscopic colorimeter and SEM, and SEM-EBSD. Results showed that the brightness of strip zone was lower than that of normal zone. Additionally, compared with normal zone, the porosity of anodizing film was higher, and cubic grains fewer, which located in the corresponding surface layer of aluminium substrate in strip zone. In order to further clarify the effect of grain orientation on the brightness of anodizing film, single crystal aluminium sheet with (100), (110) or (111) orientation was anodized. Results showed that the anodized (100) oriented specimen, i.e., cubic grain was brighter, whose anodizing film had lower porosity, compared with (110) and (111) oriented ones. Therefore, the formation mechanism of strip defects was proposed as uneven distribution of cubic grains. The zones with fewer cubic orientated grains were darker, and were visible as strip defects after anodizing.